COMBINED STABILIZATION OF THE PELVIC RING DISRUPTION INCLUDING TECHNIQUE OF SACRAL BARS: A CASE REPORT - Merdžanoski, Igor; Trpeski, Simon; Arsovski, Oliver; Kafrandzijev, Igor (Acta medicae Medianae, 2023)
The aim of this case presentation is to demonstrate that the technique of sacral bars, combined with anterior fixation with a plate, is an effective method of posterior pelvic stabilization in cases of severe pelvic ring disruption. We are presenting a case of a young individual who sustained severe pelvic ring disruption (Type A III according to the Tile classification) with sacral fracture following compression injury of the lower torso. Initially, explorative laparotomy for splenic injury was performed, while surgery for pelvic stabilization was postponed for 5 days. The surgery for pelvic stabilization included fixation of the symphysis with a plate followed by posterior fixation with two sacral bars. No postoperative complications were noted. The patient was followed for a year post injury, and he made full recovery returning to complete preinjury level of activity Posterior stabilization with sacral bars in pelvic ring disruptions combined with anterior plate of the symphysis is safe and effective method for the treatment of this type of injury.